2013
DOI: 10.3329/jssmc.v4i2.14401
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcome of Obstructed Labour at a tertiary care Hospital

Abstract: Background: Obstructed labour is one of the most common preventable cause of maternal and prenatal morbidity and mortality in developing countries. Objective: The purpose of the present study was to determine the risk factors as well as to asses the outcome of obstructed labour. Method: This cross sectional study was conducted in the Department of Gynecology & Obstetrics at Shaheed Ziaur Rahman Medical College Hospital, Bogra during the period from January 2007 to December 2007. One hundred and five cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
26
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 11 publications
15
26
5
Order By: Relevance
“…In the present study CPD was the most leading cause of obstruction comprising 54.4% 0f cases which is comparable Dafallah et al Neena chuni (2008) and Shimelis et al (2010). [5][6][7] Malpresentation and malposition have taken together contributed 42% of cases in the present study which is similar to the incidence of 45.4% and 50.5% as reported by Neena chuni (2008) and Islam et al (2012). [6,8] In the present study caesarean section was done in 80.4% of cases which is comparable with the Neena chuni (2008) series where CS was done in 82.1% of cases.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In the present study CPD was the most leading cause of obstruction comprising 54.4% 0f cases which is comparable Dafallah et al Neena chuni (2008) and Shimelis et al (2010). [5][6][7] Malpresentation and malposition have taken together contributed 42% of cases in the present study which is similar to the incidence of 45.4% and 50.5% as reported by Neena chuni (2008) and Islam et al (2012). [6,8] In the present study caesarean section was done in 80.4% of cases which is comparable with the Neena chuni (2008) series where CS was done in 82.1% of cases.…”
Section: Discussionsupporting
confidence: 80%
“…[5][6][7] Malpresentation and malposition have taken together contributed 42% of cases in the present study which is similar to the incidence of 45.4% and 50.5% as reported by Neena chuni (2008) and Islam et al (2012). [6,8] In the present study caesarean section was done in 80.4% of cases which is comparable with the Neena chuni (2008) series where CS was done in 82.1% of cases. [6] In the modern era, CS under good antibiotics coverage has a very low morbidity and mortality and it is the best option.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Majority of the patients were primigravidas (49.2%) comparable to the study of Anjum Ara (1996) 10 where 40.8% patients of obstructed labour were primigravidas. Majority were from rural areas (87.5%) comparable to the findings of Islam JA et al( 2012) 11 who reported 88% from rural areas. Majority were either illiterate or with only primary education (66.7%) comparable to highest incidence in low education patients (87%) in the study of Islam JA et al (2012) 11 .…”
Section: Results:-supporting
confidence: 76%
“…Majority were from rural areas (87.5%) comparable to the findings of Islam JA et al( 2012) 11 who reported 88% from rural areas. Majority were either illiterate or with only primary education (66.7%) comparable to highest incidence in low education patients (87%) in the study of Islam JA et al (2012) 11 . Most patients were unbooked (52.5%) comparable to 63.8% in the study of Saad E Dafallah et al (2003) 9 .…”
Section: Results:-supporting
confidence: 76%